The potential impact of the COVID-19 pandemic on GDP per capita in European countries - Zagurska-Antoniuk, Victoria; Suprunova, Iryna; Zavalii, Tetiana (Public Policy and Accounting, 2020)
The study simulates the potential impact of the COVID-19 pandemic on gross domestic product (GDP) per capita in European countries for the first half of 2020. It is realized through regression analysis. The dependent variable was GDP per capita (forecast by International Monetary Fund) and the independent variables were five factors that characterize the spread of the COVID-19 pandemic in European countries (total confirmed cases per capita; total confirmed deaths per capita; percentage of recovered in the total confirmed cases on July 1, 2020; total tests per capita; percentage of days from the beginning of the spread of COVID-19 in the total number of days in the first half of 2020). Based on the results of the regression analysis, the regression equation explains 56 % of the changes in the dependent variable. The proposed regression model is recognized as adequate to sample data. The multicollinearity among independent variables is denied. Thus, the proposed regression model can be used to determine the impact of the COVID-19 pandemic on GDP per capita, when information on real GDP per capita becomes known.